2010
DOI: 10.1080/00927870902829056
|View full text |Cite
|
Sign up to set email alerts
|

Depth and Stanley Depth of Multigraded Modules

Abstract: Abstract. We study the behavior of depth and Stanley depth along short exact sequences of multigraded modules and under reduction modulo an element.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
54
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(54 citation statements)
references
References 9 publications
0
54
0
Order By: Relevance
“…In the third section, we prove that if I ⊂ K [ 1 2 3 ] is saturated, then sdepth(I) ≥ 2, see Proposition 3.1. As a consequence, sdepth(I) ≥ sdepth(K [ 1 2 3 ]/I) + 1 for any monomial ideal in I ⊂ K [ 1 2 3 ], see Corollary 3.1, thereby giving in this special case an affirmative answer to a question raised by Rauf in [13].…”
Section: Introductionmentioning
confidence: 83%
“…In the third section, we prove that if I ⊂ K [ 1 2 3 ] is saturated, then sdepth(I) ≥ 2, see Proposition 3.1. As a consequence, sdepth(I) ≥ sdepth(K [ 1 2 3 ]/I) + 1 for any monomial ideal in I ⊂ K [ 1 2 3 ], see Corollary 3.1, thereby giving in this special case an affirmative answer to a question raised by Rauf in [13].…”
Section: Introductionmentioning
confidence: 83%
“…In this work we focus on the relationship between sdepth I and sdepth S/I for an arbitrary monomial ideal I. In [19], Rauf showed that if I is a complete intersection monomial ideal, then sdepth(I) > sdepth(S/I). Subsequently, Herzog's survey article [5] stated the weaker inequality sdepth(I) ≥ sdepth(S/I) (for arbitrary monomial ideals) as Conjecture 64, noting that the inequality is strict in all known cases.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, we state and prove a generalization of our main theorem. We remark that the proofs of the main theorem and its extension are minor modifications of the original proofs for depth, replacing depth by sdepth and the depth lemma by [7,Lemma 2.2]. Nevertheless, here we give complete proofs in order to make the treatment clear and self-contained.…”
Section: Introductionmentioning
confidence: 99%